2022
DOI: 10.1021/acsomega.2c01095
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Surface-Enhanced Raman Scattering Substrates for the Trace Detection of Ammonium Nitrate, Thiram, and Nile Blue

Abstract: We report the fabrication and performance evaluation of hybrid surface-enhanced Raman scattering (SERS) substrates involving laser ablation and chemical routes for the trace-level detection of various analyte molecules. Initially, picosecond laser ablation experiments under ambient conditions were performed on pure silver (Ag) and gold (Au) substrates to achieve distinct nanosized features on the surface. The properties of the generated surface features on laser-processed portions of Ag/Au targets were systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 66 publications
1
8
0
Order By: Relevance
“…The intense Raman peak of thiram at 1370 cm −1 can be associated with the CH 3 symmetric in-plane deformation and C-N stretching. 40 The Raman spectra of thiram is shown in Fig. S1 (ESI †) and observed vibrational peaks with their corresponding mode assignments are tabulated in Table T2 (ESI †).…”
Section: Sers Studiesmentioning
confidence: 99%
“…The intense Raman peak of thiram at 1370 cm −1 can be associated with the CH 3 symmetric in-plane deformation and C-N stretching. 40 The Raman spectra of thiram is shown in Fig. S1 (ESI †) and observed vibrational peaks with their corresponding mode assignments are tabulated in Table T2 (ESI †).…”
Section: Sers Studiesmentioning
confidence: 99%
“…Hence, with the rapid developments in the modern world, chemical, environmental, and microbiological contaminants are significant pollutants that should be moderated and detected easily. The rapid growth and involvement of molecular sensing encouraged numerous researchers to explore various technologies toward the fabrication of economical, reproducible, and highly sensitive SERS-active substrates for label-free molecular detection (Vendamani et al, 2018a, 2018b, Ravi Kumar et al, 2021Moram et al, 2018;Bharati et al, 2018;Beeram et al, 2022;Rathod et al, 2022;Banerjee et al, 2022). The plasmonic nanostructures (NSs) with different dimensions on rough surfaces attracted researcher's interests owing to the exploration of SERS by Fleischmann et al in the seventies, witnessed through Raman enhancement of pyridine in the order of $10 6 on a rough metal silver electrode (Fleischmann et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Ag NPs in DIW, a broader absorption spectrum was noticed compared to alkali metal hydroxide, possibly due to the ablation medium's ionic (Na + and K + ) species and the variation in the size distribution [16]. In the case of Au nanostars, the peak in the visible region (582 nm) corresponds to the core, and in the NIR region (763 nm) is owing to the sharp tips of Au nanostars, Fig 1(d) [17,18]. FESEM images revealed that the Au nanostars were decorated randomly throughout the area on plain and laser-processed Au substrate.…”
Section: Resultsmentioning
confidence: 97%